Xylazine or detomidine in dairy calves: a comparison of clinically relevant pharmacodynamic parameters under sedation - Gittel, Claudia; Brehm, Walter; Wippern, Maike; Roth, Susanne; Hillmann, Aline; Michaele, Alef (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2021)
Objective Chemical restraint in dairy calves is necessary to enable diagnostic and surgical procedures. It is unclear whether xylazine or detomidine differ with regard to desirable and unwanted effects.Material and methods In a prospective randomized interventional study, 10 healthy Holstein-Friesian calves (age range 3–6 month) were sedated with either xylazine (0.1 mg/kg, Group X, n = 5) or detomidine (0.03 mg/kg, Group D, n = 5) intravenously, followed by butorphanol (0.1 mg/kg i. v.) in all animals. Characteristics of sedation and selected pharmacodynamic parameters were compared between groups using a non-parametric Mann-Whitney U test.Results All calves (5/5) in Group X and (3/5) calves in Group D became laterally recumbent within 5 minutes. Two calves (40 %) in Group D remained standing and could not been positioned in lateral recumbency 15 minutes after initial administration of the sedation agents. Sedation scores, onset and duration of sedation did not differ between groups. Heart and respiratory rate decreased in both groups. Mean arterial pressure was with around 30 mmHg significantly higher in Group D (t25, t30, t35, t40 with p = 0.018, 0.036, 0.029 and 0.016, respectively). In Group X, glucose level (t60) and packed cell volume (t30) were significantly lower (p = 0.032 and 0.048, respectively).Conclusion and clinical relevance The xylazine-butorphanol combination provided reliable recumbent chemical restraint. With detomidine-butorphanol recumbency failed in some individuals, but a sufficient clinical sedation was achieved. Based on the limited monitoring used in this study, the side effects are of minor clinical relevance in healthy individuals.
Keywords: Alpha2-agonist; bone marrow aspiration; bovine; glucose; recumbency